Between Air and Electricity Microphones and Loudspeakers as Musical Instruments - can Eck, Cathy (Bloomsbury Academic, 2017)
After the sound reproduction industry had claimed "perfect high fidelity" for sound recordings already at the beginning of the twentieth century, composers and sound artists challenged this perfection by tweaking microphones and loudspeakers to make them act as a musical instrument instead of a mere sound reproduction device. This book explores the instrumental use of microphones and loudspeakers in music beginning in the 1950s. The popular noise musician Merzbow, over-minimalist classic Alvin Lucier, cult instrument inventor Hugh Davies, and contemporary visual artist Lynn Pook made audible what was supposed to remain silent.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Music / Instruction & Study / Composition; Music; Electronic books